Development of a tribal region Banpur block, district Puri, Orissa (New Delhi, 1977)
Development of tribal areas has always posed as a special problem. The Ministry of Community Development of the Government of India demarcated separate tribal blocks for intensive work. However, due to difficult accessibility to and within the tribal blocks, and the need for very intimate understanding and solution of the problems, the AVARD Planning team feels that the size (area-wise) of an average tribal block in the country is too big. For an efficient, well conceived plan, a physically and socially compact cluster of 33 villages was taken in Banpur block, Orissa. Eleven of these revenue villages are uninhabited, but even the remaining twenty two are really hamlets separated by sometimes long distance. One of the novel schemes recommended in this report is of the shifting of population in and from seven villages so that even rudimentary facilities of potable drinking water, primary education and health can be provided to the population. This is Independent of proposed central villages which will have coll ection cum sale stores run by the voluntary agency operating in the area. Unlike many other micro levelplans of AVARD, agents of growth including schemes of non-formal education, extension,) merger of villages, small stretches of roads etc. take about one fourth of the total outlay of about Rs. 20 lakhs. Agricultural development claims about Rs. 3 lakhs and irrigation Rs 9 lakhs.) This is the minimum to give the economy an initial push. The plan takes note of the capabilities of the local implementing agency, which in any case cannot take up any large scale Irrigarion, technical training and land shaping projects. Most schemes were drafted after taking views of the local opinion leaders. The local population has shown its willingness even for the unorthodox programme of the shifting of population.
Keywords: Community development